Exploring a framework for demandable services from antenatal to postnatal care: a deep-dive dialogue with mothers, health workers and psychologists - Chancy Mauluka; William Stones; Isabel Kazanga Chiumia; Limbika Maliwichi (BMC, 2023)
Abstract Background One of the factors affecting quality of care is that clients do not demand care practises during antenatal, intrapartum and postnatal care. This study aimed to identify care practices that can be demanded by the mother in the continuum of care from antenatal to postnatal. Methods The study respondents included 122 mothers, 31 health workers and 4 psychologists. The researchers conducted 9 Key Informant Interviews with service providers and psychologists, 8 Focus Group Discussions with 8 mothers per group, and 26 vignettes with mothers and service providers. Data was analysed using Interpretative Phenomenological Analysis (IPA) where themes were identified and categorised. Results During antenatal and postnatal care, mothers demanded all recommended services presented to them. Some services seen as demandable during labour and delivery included 4-hourly assessments of vital signs and blood pressure, emptying of the bladder, swabbing, delivery counselling, administration of oxytocin, post-delivery palpation, and vaginal examination. For the child mothers demanded head to toe assessment, assessment of vital signs, weighing, cord stamp and eye antiseptics, and vaccines. Women observed that they could demand birth registration even though it was not among the recommended services. Respondents proposed empowerment of mothers with cognitive, behavioural and interpersonal skills to demand services e.g., knowledge of service standards and health benefits in addition to improved self-confidence and assertiveness. In addition, efforts have to be made to address perceived or real health worker attitudes, mental health for the client and the service provider, service provider workload, and availability of supplies. Conclusion The study found that if a mother is informed in simple language about services that she is supposed to receive, she can demand numerous services in the continuum of care from antenatal to postnatal. However, demand cannot be a standalone solution for improving quality of care. What the mother can ask for is a step in the guidelines, but she cannot probe deeper to influence quality of the procedure. In addition, empowerment of mothers needs to be coupled with services and systems strengthening in support of health workers.